2013
DOI: 10.1186/1479-5876-11-271
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I increases markers of osteoblastic activity and reduces bone resorption via osteoprotegerin and RANK-ligand

Abstract: BackgroundBone is one of the major target tissues for Insulin-like Growth Factor I (IGF-I). Low doses of IGF-I were able to improve liver-associated osteopenia. In the present work, a model of partial IGF-I deficiency was used in order to provide insight into the mechanisms of the beneficial actions of IGF-I replacement therapy in bone.MethodsSeveral proteins involved in osteoblastic/osteocyte and osteoclastic differentiation and activity were studied in the three experimental groups: control (CO) group (wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 68 publications
(70 reference statements)
3
42
0
7
Order By: Relevance
“…The preference for IGF-1 treatment at low doses was chosen following the experience acquired from previous studies belonging to the same model [46, 8, 9, 11, 13, 14, 18, 21, 24, 35, 39, 40, 45]. Briefly, such dosage is enough to restore normal circulating IGF-1 values without inducing hypoglycemia and any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preference for IGF-1 treatment at low doses was chosen following the experience acquired from previous studies belonging to the same model [46, 8, 9, 11, 13, 14, 18, 21, 24, 35, 39, 40, 45]. Briefly, such dosage is enough to restore normal circulating IGF-1 values without inducing hypoglycemia and any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its deficiency has been initially related to different pathologies, such as Laron’s syndrome, intrauterine growth restriction (IUGR), liver cirrhosis, metabolic syndrome, and aging-related disorders, among others [22, 24, 28, 32, 38, 42, 43, 47, 49]. …”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 could stimulate the formation of osteocalcin, collagen and non-collagenous matrix proteins by differentiated osteoblasts and increase the number of functional osteoblasts by promoting osteoprogenitor cell replication [45]. It has been found that IGF-1 deficiency was associated with hypoexpression of OPG and Runx2 genes and overexpression of RANKL resulting in promotion of the osteoclastic activity and osteoblastic inhibition [46]. Furthermore, high glucose concentrations significantly impair the proliferative and functional responses of osteoblastic cells to IGF-I [47] and inhibit the osteogenic differentiation [48].…”
Section: Discussionmentioning
confidence: 98%
“…According to previous series [26,27], 5 6 1 month old heterozygous mice (Hz) showed a significant decrease of circulating levels of IGF-1 as compared with control animals (WT), which was normalized by the exogenous administration of low doses of IGF-1 (2 mg/100 g body weight/day, for 10 days). Thus, the usefulness of the substitutive IGF-1 therapy was confirmed ( Fig.…”
Section: Igf-1 Circulating Levels Body and Brain Weightsmentioning
confidence: 95%
“…With this perspective, the present study was aimed to evaluate, in a novel experimental model of mice with partial IGF-1 deficiency [26,27], the following: 1) brain morphological damage, assessed by histopathological studies (number and shape of cells by Nissl staining) and nuclear magnetic resonance imaging (MRI, hydric content and ventricular area); 2) oxidative damage by lipid oxidative (MDA) and hypoxic/ischemic damage (lactate) markers; 3) cerebral gene expression of proteins involved in cellular protection (such as HSPs), inflammation and cell death; and 4) brain function determined by learning and memory tests.…”
Section: Introductionmentioning
confidence: 99%